High performance wire-type supercapacitor with Ppy/CNT-ionic liquid/AuNP/carbon fiber electrode and ionic liquid based electrolyte. (April 2019) - Song, Changhoon; Yun, Junyeong; Keum, Kayeon; Jeong, Yu Ra; Park, Heun; Lee, Hanchan; Lee, Geumbee; Oh, Seung Yun; Ha, Jeong Sook
Abstract: We report a fabrication of a high-performance wire-type supercapacitor through surface modification of carbon fiber with ionic liquid, nanomaterials, and gel electrolyte containing ionic liquid. Coating of Au nanoparticles onto carbon fiber increases both surface area and electrical conductivity. Dip-coating of mixture of ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([EMIM][TFSI]), carbon nanotubes, and electropolymerization of polypyrrole (Ppy) onto Au coated fiber for pseudocapacitance results in high capacitance. The use of propylene carbonate-poly(methyl methacrylate)-[EMIM][TFSI] gel electrolyte gives high operation voltage. Such wire-type supercapacitor exhibits a high voltage of 2.5 V, an areal capacitance of 38.49 mF cm −2, and a maximum energy and power density of 24.7 μWh cm −2 and 3.52 mW cm −2, respectively. In addition, the cyclic stability of the supercapacitor is dramatically enhanced by using 2-naphthalene sulfonic acid as a dopant in electropolymerization of Ppy. Encapsulation with a thermally shrinkable tube endows the supercapacitor with mechanical stability and waterproof features when it is bent, folded, twisted, even in water. This work demonstrates high potential of such wire-type supercapacitor as a flexible energy-storage device for various applications, especially those that require high voltage. Graphical abstract: Image 1